Towards Self-X cognitive manufacturing network: An industrial knowledge graph-based multi-agent reinforcement learning approach. (October 2021) - Zheng, Pai; Xia, Liqiao; Li, Chengxi; Li, Xinyu; Liu, Bufan
Highlights: A Self-X cognitive manufacturing network to achieve cognitive mass personalization. Industrial knowledge graph and graph-embedding techniques for Self-X cognitive manufacturing network establishment. Multi-agent reinforcement learning enabled approach for self-optimized manufacturing task fulfilment. Abstract: Empowered by the advanced cognitive computing, industrial Internet-of-Things, and data analytics techniques, today's smart manufacturing systems are ever-increasingly equipped with cognitive capabilities, towards an emerging Self-X cognitive manufacturing network with higher level of automation. Nevertheless, to our best knowledge, the readiness of 'Self-X' levels (e.g., self-configuration, self-optimization, and self-adjust/adaptive/healing ) is still in the infant stage. To pave its way, this work stepwise introduces an industrial knowledge graph (IKG)-based multi-agent reinforcement learning (MARL) method for achieving the Self-X cognitive manufacturing network. Firstly, an IKG should be formulated based on the extracted empirical knowledge and recognized patterns in the manufacturing process, by exploiting the massive human-generated and machine-sensed multimodal data. Then, a proposed graph neural network-based embedding algorithm can be performed based on a comprehensive understanding of the established IKG, to achieve semantic-based self-configurable solution searching and task decomposition. Moreover, a MARL-enabled decentralized system is presented to self-optimize the manufacturing process, and to further complement the IKG towards Self-X cognitive manufacturing network. An illustrative example of multi-robot reaching task is conducted lastly to validate the feasibility of the proposed approach. As an explorative study, limitations and future perspectives are also highlighted to attract more open discussions and in-depth research for ever smarter manufacturing.